SELF PERCEPTION ABOUT THE COMPETENCE OF MECHANICAL ENGINEERING EDUCATION STUDENTS AS PROSPECTIVE TEACHERS - Suryanto, Ahmad Eko; Lumbantobing, Marko Ayaki (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
This study aims to describe the competencies possessed by mechanical engineering education students based on self-perception. These competencies are pedagogic competence, personality competence, sosial competence and professional competence. The results showed that students of the Mechanical Engineering Education Study Program (PTM), Palangka Raya University (UPR) had quite good pedagogical competence, good personality competence, good sosial competence and fairly good professional competence.